Tinjauan Yuridis Perjanjian Jual Beli Berdasarkan Surat Pemesanan Barang Purchase Order) Antara PT. Union Confectionery Dengan PT. Industri Pembungkus Internasional - Mitha Syahfitri; Anggreini Atmei Lubis; Aldi Subhan Lubis (JUNCTO: Jurnal Ilmiah Hukum, 2022)
The purpose of this study is to find out whether a Purchase Order (PO) can be categorized as a sale and purchase agreement, what is the mechanism for implementing a sale and purchase agreement between PT. Union Confectionery with PT. International Packaging Industry (PT. IPI) and what are the rights and obligations of the parties in the sale and purchase agreement between PT. Union Confectionery with PT. IPI. The type of research in writing this thesis is normative juridical which is descriptive analysis in nature. The approach method in this study is the statutory approach. A Purchase Order (PO) can be categorized as a sale and purchase agreement because a Purchase Order has the same elements as a sale and purchase agreement as based on the principle of consensualism in the Civil Code. The mechanism for implementing the sale and purchase agreement between PT. Union Confectionery with PT. IPI is the provision of boxes and wrappers using the Purchase Order (PO) system. PT. Every time Union Confectionery places an order with PT. IPI by issuing Purchase Orders (PO) which include specifications, designs, details and quantities of goods. The payment method is 45 (forty five) days after receiving the goods. Rights and Obligations of the Parties in the Cooperation Agreement between PT. Union Confectionery with PT. IPI is PT. Union Confectionery has the right to accept cardboard orders from PT. IPI according to the specifications set by PT. Union Confectionery on Purchase Orders (PO), has the right to request returns for cardboard that does not meet specifications and is obliged to pay for the order. Rights and Obligations of PT. IPI is entitled to receive payments in accordance with the agreed timely, is obliged to make cardboard according to the specifications set by PT. Union Confectionery and is obliged to replace any cartons that do not conform.